2010
DOI: 10.2174/092986710791556023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Purine Salvage Pathway: A Valuable Approach for Antiprotozoal Chemotherapy?

Abstract: For many years, the purine salvage pathway of parasitic protozoa has been regarded as an attractive chemotherapeutic target. Parasitic protozoa lack de novo synthesis and rely entirely on the purine salvage pathway to meet their purine demands. Because of the great phylogenetic difference between parasite and host, there are often sufficient distinctions that can be exploited to design specific inhibitors for the parasitic enzymes. As a result, this pathway has been thoroughly investigated over the last twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 127 publications
(222 reference statements)
2
90
0
Order By: Relevance
“…Interestingly, the corresponding metabolite pyrroline-5-carboxylate was found to be increased in our study. Martin et al (54) also showed that purine starvation augmented the interconversion of hypoxanthine and ampicillin (AMP) to imipenem (IMP), both key nucleotides of the purine salvage pathway of L. donovani (55). High levels of hypoxanthine were also found in the resistant lines of our study (IMP and AMP were not detected).…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, the corresponding metabolite pyrroline-5-carboxylate was found to be increased in our study. Martin et al (54) also showed that purine starvation augmented the interconversion of hypoxanthine and ampicillin (AMP) to imipenem (IMP), both key nucleotides of the purine salvage pathway of L. donovani (55). High levels of hypoxanthine were also found in the resistant lines of our study (IMP and AMP were not detected).…”
Section: Discussionsupporting
confidence: 69%
“…The purine base is available for salvage by phosphoribosyltransferases, in both the host and the parasite. 2527 The purine phosphoribosyltransferase from P. falciparum accepts hypoxanthine, guanine, and xanthine, in decreasing order of physiological significance. 28,29 Their products are purine nucleoside monophosphates, and these serve as precursors for conversion to all purines as RNA and DNA precursors (Figure 2).…”
Section: Protozoan Purine Nucleoside Phosphorylase and Malariamentioning
confidence: 99%
“…25 However, based on the genome sequence data, it seems that trypanosomatids possess by-pass mechanisms involving other enzymes and transporters. 26 This poses the question as to whether inhibition of a single enzyme of the purine salvage pathway is enough to kill trypanosomatids or whether inhibition of multiple enzymes by combination therapy would be required.…”
Section: Drug Target Discovery Using Genome Informationmentioning
confidence: 99%